MEANS OF PREPARING FUTURE ENGINEERS FOR PROFESSIONAL ACTIVITIES ON THE BASIS OF AN INTEGRATIVE APPROACH - Adilov Nabijon Khursanovich (Journals Park Publishing, 2022)
This article will focus on the integration of the content of engineering courses in higher professional education
Keywords: internal disciplinary integration, integration, integrative processes.